Dynamic changes in tumor profiling reveal intra- and inter-tumoral heterogeneity focused on an uncharacterized HER2 mutation: a case report of a young breast cancer patient - Schaffrin-Nabe, Dörthe; Josten-Nabe, Anke; Tannapfel, Andrea; Uhl, Waldemar; Garmer, Marietta; Kurzrock, Razelle; Crook, Timothy; Limaye, Sewanti; Schuster, Stefan; Patil, Darshana; Schaffrin, Merle; Mokbel, Kefah; et al. (Frontiers in Oncology, 2024)
Despite multiple recent advances in systemic therapy for metastatic breast cancer, cases which display suboptimal response to guideline-driven treatment are frequently seen in the clinic. Effective options for such patients are limited, particularly in later line of therapy, and selection of optimal treatment options is essentially empirical and based largely on considerations of previous regimens received. Comprehensive cancer profiling includes detection of genetic alterations in tissue and circulating tumor DNA (ctDNA), immunohistochemistry (IHC) from re-biopsied metastatic disease, circulating tumor cells (CTCs), gene expression analysis and pharmacogenomics. The advent of this methodology and application to metastatic breast cancer, facilitates a more scientifically informed approach to identification of optimal systemic therapy approaches independent of the restrictions implied by clinical guidelines. Here we describe a case of metastatic breast cancer where consecutive comprehensive tumor profiling reveals ongoing tumor evolution, guiding the identification of novel effective therapeutic strategies.